The Nature of Childhood Leukemia and Lymphoma - Kersey, J. H. (1978)
One hundred consecutive newly diagnosed cases of leukemia and lymphoma in children from 0 to 16 years of age presenting at the University of Minnesota from 1973 to 1977 were studied. Clinical features were correlated with phenotypic features of blast cells, including surface markers and cytomorphology. Four groups with distinct clinical and pathologic features emerged from the study: a) The acute leukemias of the “null” or “undifferentiated” group were those in which the malignant cells carried distinctive null leukemia surface antigen and lacked features of either T cells (E-rosette positivity) or B cells (surface immunoglobulin positivity). These cases occurred most frequently in the series (56% of total cases), peaked in incidence at 6 years, were associated with extensive bone marrow involvement, lacked distinguishing cytomorphologic features, and had the best response to therapy of all groups. b) The acute myelogenous leukemias, including those with myeloid, monocytoid, or erythroid features or a combination of the above, had extensive bone marrow involvement and the characteristic morphology. This group was seen with intermediate frequency and showed an intermediate response to therapy. c) Leukemia-lymphomas of the T-cell group were frequently associated with mediastinal masses and other masses, a cytomorphology which was different from the B-cell group but similar to the null group, and high white cell counts. These cases occurred with intermediate frequency (14%) and had a worse prognosis than the null group. d) Leukemia-lymphomas of the B-cell group had monoclonal surface immunoglobulin with μ-heavy and either κ or λ light chain. These patients were least frequent in the series, frequently presented with abdominal masses, and had a characteristic Burkitt cell morphology. Prognosis was the worst of all patients in our series. These data suggest that the major phenotypic groups of childhood leukemia and lymphoma have differing prognoses and should receive differing forms of therapy. Clinical and pathologic features of each group are sufficiently distinctive to suggest that they may have different causes.